La gestion esthétique et biomécanique d’un cas d’édentement de classe II de Kennedy Applegate - Sana BEKRI; Hiba TRIKI; Rim BIBI; Monir TRABELS (International Arab Journal of Dentistry (IAJD), 2016)
The primary goal when treating a partial edentulism is to res- tore the occlusal function. However, when the edentulism is bordered by an anterior tooth, the goal must include res- toring aesthetics. In this situation, the axial attachment can give satisfactory results. Indeed, thanks to its design, the two factors, aesthetics and function are constantly assured. But for the success of rehabilitation, it is essential to respect the stages of the implementation of axial attachments in mee- ting the demands and requirements of the composite prosthesis. In this paper, a case of a Class II Kennedy Applegate edentulism is presented, in which the aesthetic and biomechanical problems were managed by the use of an axial attachment.